Crystal structure of Ce9Ir37Ge25 - Voßwinkel, Daniel; Block, Theresa; Pöttgen, Rainer (Zeitschrift für Kristallographie. New crystal structures, 2025)
Ce Ir Ge , hexagonal, (no. 187), = 18.3707(16) Å, = 3.9695(4) Å, and = 1160.16(18) Å , = 1, ) = 0.0315, ) = 0.0799, = 293 K.